The implementation of project-based learning through animated videos in reading for specialized information - Suharto, Ririn Pratiwi; Zubaidi, Zubaidi; Maulidiyah, Fitrotul; Setiawan, Ardian Wahyu; Putra, Dhony Manggala (Journal of Research on English and Language Learning (J-REaLL), 2024)
This research investigated the implementation of project-based learning through animated videos in reading for specialized information and the perception of students on it. This research differed from others because students visualized the information from the reading text into animated videos. The implementation of project-based learning through animated video was measured by observation. Students’ perceptions about it were measured from the questionnaire. Thirty-two vocational students took part in this research. Based on the results of observations, three steps of project-based learning supported students’ success in achieving the learning outcomes. The result showed that students’ positive responses about the process of creating animated videos were: they worked with group (65,6%); they tried to design their animated videos (62,5%); they accessed and used features properly (59,4%); and they enjoyed to learn reading for specialized information (71,9%). Students’ positive responses about the benefits of creating animation videos were: they established good communication (62,5%); they got a better understanding (71,9%); they felt easier to visualize the lesson material (62,5%); they were more motivated to read (53,1%), and they felt more enthusiastic to learn new vocabularies (65,6%). On the other hand, students’ negative responses showed that they spent a lot of time in making animated videos (9,4%). Lecturers recommended using easy and basic applications in creating animated videos, such as Canva. The implication of the research was students developed their creativity to visualize a reading text in the form of animated videos, and they understood the reading text.